Victims of child sexual abuse: Understanding their need for justice - Tamarit Sumalla, Josep Maria (International journal of law, crime and justice, 2018)
This study examined, via 23 in-depth interviews, how victims express their expectations concerning the criminal justice system (CJS), focusing on adults who suffered sexual abuse as children. Previous research has rarely studied how sexual assault victims and, particularly, victims of child sexual abuse, perceive CJS. In this study the perceptions of both victims who had contact with the CJS and those who had not reported the crime were examined. We found that victims' expectations are highly focused on the verdict imposing a prison sentence, but the demand for punishment can be viewed as a symbolic subrogation of a desire for justice, largely associated with the need for recognition and validation, which the CJS is able to satisfy only in a very limited way. The study confirms the importance of properly implement the provisions of EU Directive 29/2012, according to which victims should be given support irrespective of whether they have reported the crime.